2020
DOI: 10.3390/ijerph17062166
|View full text |Cite
|
Sign up to set email alerts
|

Who Benefits from An Intervention Program on Foundational Skills for Handwriting Addressed to Kindergarten Children and First Graders?

Abstract: This study examined the effectiveness of a 10-wk intervention program based on occupational therapy principles on visual-motor integration skills and fine motor abilities in kindergartners and first graders. We recruited 55 students tested three times with the Visual-Motor Integration Test (VMI) and Movement Assessment Battery for Children-2 (MABC-2): before the intervention (T1), post-intervention (T2) and one month later (T3). Research findings: Significant improvements were found on VMI between T1 and T2, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 70 publications
1
20
0
1
Order By: Relevance
“…Furthermore, a steady increase of studies has demonstrated that motor skills interventions implemented in school settings, outside a physical education setting but still teacher-led, can improve a variety of motor skills in children and adolescents [78]. This has proven especially effective for pupils with motor difficulties or at-risk levels of motor skill [79]. Importantly, these latter sub-groups of children and adolescents also benefit from whole class approaches [80].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a steady increase of studies has demonstrated that motor skills interventions implemented in school settings, outside a physical education setting but still teacher-led, can improve a variety of motor skills in children and adolescents [78]. This has proven especially effective for pupils with motor difficulties or at-risk levels of motor skill [79]. Importantly, these latter sub-groups of children and adolescents also benefit from whole class approaches [80].…”
Section: Discussionmentioning
confidence: 99%
“…Searching for an inclusive solution, some studies have introduced occupational therapists (OTs) in the classrooms [53][54][55]. With the aim to provide targeted services, in small groups, to those children struggling in participating at the required classroom activities.…”
Section: Implication For Practicementioning
confidence: 99%
“…Moreover, a recent study of Dehghan and colleagues demonstrated that children with cancer (8–18 years old) had a variety of problems in three occupational areas (i.e., self-care, productivity, and leisure), confirming the results of our exploratory research [ 74 ]. Fine motor skills are sensitive to rehabilitation and targeted intervention [ 56 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%